Tren Perkembangan : System Literature Review Analisis Pemanfaatan Green Accounting Terhadap Kinerja Keuangan Perusahaan (Jurnal Kendali Akuntansi, 2024)
Purposes : The purpose of this research is to review and analyse previous information included in the study of Green Accounting in Indonesia which is still in the process of developing and becoming a hot topic in Indonesia. The author hopes that this research can serve as a basis and provide ideas for future research Research Methods : This study was using the SLR (Systematic Literature Review) method with 60 totals previous journals taken literatured in this study. Research Results : The trend of Green Accounting studies in Indonesia from 2019-2024 is still fluctuating. This System Literature Review research shows that Green Accounting needs to be improved. This research is based on policies, initiatives to manage the sustainability of the natural environment based on eco-friendly principles and green innovations that can further improve the environment. The business activities of a company in the future will no longer cause damage to the natural environment, but the entity can preserve and maintain the surrounding ecosystem and natural resources.